Lecture notes on experimental design, data analysis, interpretation and presentation of experimental results - Rege, J.E.O. (International Livestock Centre for Africa, 1991)
The note is divided into five parts, viz, sampling methods, multicollinearity or intercorrelation, autocorrelation, and estimable and testable functions. The first part discusses sampling procedures, sample size determination, random sampling, sampling by deliberate stratification, blocking and its effect on sample size. The second part discusses the effect of multicollinearity on least square constants and sums of squares, simultaneous tests on regression coefficients, types of tests in regression models and coefficient of determination. The problems of autocorrelation, estimation of regression and autocorrelation parameters and data analysis for on-farm experiments are discussed in part three. Part four looks at estimable and testable functions.